2018
DOI: 10.1002/biof.1468
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and local hepcidin as emerging and important peptides in renal homeostasis and pathology

Abstract: Recent data suggest that the importance of hepcidin goes beyond its classical role in controlling systemic iron metabolism. Local hepcidins are emerging as important peptides for organ homeostasis in the brain, heart, blood vessels, and in cancer as well. Similarly, accumulating data indicate that hepcidin does seem to be an important factor in renal homeostasis. This review encompasses present knowledge concerning the role of hepcidin in renoprotection and its use as a biomarker of kidney diseases. Understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Also, Veuthey et al hypothesized that the proximal tubule produces prohepcidin. However, it should be noted that the authors of this study measured the immunohistochemical expression of this peptide rather than its mRNA expression, which may indicate that the peptide's presence inside proximal tubular cells is caused by absorption from the blood filtrate, which contains the peptide's systemic form (103,104). However, hepcidin expression is not restricted to tubular cells, as there is evidence that it can also be found in the leukocytes of the renal interstitium when the kidney is inflamed (105).…”
Section: Hepcidin Regulation In Kidney Cancermentioning
confidence: 91%
See 2 more Smart Citations
“…Also, Veuthey et al hypothesized that the proximal tubule produces prohepcidin. However, it should be noted that the authors of this study measured the immunohistochemical expression of this peptide rather than its mRNA expression, which may indicate that the peptide's presence inside proximal tubular cells is caused by absorption from the blood filtrate, which contains the peptide's systemic form (103,104). However, hepcidin expression is not restricted to tubular cells, as there is evidence that it can also be found in the leukocytes of the renal interstitium when the kidney is inflamed (105).…”
Section: Hepcidin Regulation In Kidney Cancermentioning
confidence: 91%
“…Hepcidin expression in the kidney is relatively low compared to the liver, which is known to be the ultimate source of hepcidin (8,102). Kulaksiz et al claim that renal hepcidin is primarily found in the connecting tubules and the cortical thick ascending limb of nephron tubules (103). Also, Veuthey et al hypothesized that the proximal tubule produces prohepcidin.…”
Section: Hepcidin Regulation In Kidney Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple damaging mechanisms of cardiac surgery-induced AKI, such as ischemia and reperfusion injury, inflammation, and oxidative stress [4]. Among various candidate biomarkers and underlying mechanisms, hepcidin and iron metabolism in AKI are recently attracting the attention of researchers as one of the main mechanisms causing renal damage in various clinical conditions [5][6][7][8][9]. However, the role of iron regulation in cardiac surgery still remains unclear [8].…”
mentioning
confidence: 99%